Efek Pemberian Pakan Komplit Berbasis Silase Campuran Sorghum dan Daun Gamal Pada Level Berbeda terhadap Konsumsi Kecernaan Protein Kasar dan Serat Kasar Ternak Kambing Lokal Betina - Langgajanji, Vimel Diki; Maranatha, Grace; Noach, Yakob Robert (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine the effect of complete feed based on a mixture of sorghum and Gamal leaf silage at different levels addition on consumption, digestibility of crude protein, and crude fiber of local female goats. In this study, 4 female local goats aged 6-8 months were used with a weight range of 11-15 kg with an average of 12.88 kg and a coefficient of variation of 6.74%. The method used is experimental with 4 treatments and 4 periods as repetition. The treatment in this study was P0 = complete feed (80% Sorghum silage + 20% concentrate), P1 = complete feed (70% Sorghum silage + 30% concentrate), P2 = complete feed (60% Sorghum silage + 40% concentrate) and P3 = complete feed (50% Sorghum silage + 50% concentrate). The parameters studied were crude protein and fiber consumption and digestibility. The data obtained were analyzed using analysis of variance. The results showed that PK consumption was P0 91.05 g/h/d, P1 97.84 g/h/d, P2 85.52 g/h/d, P3 81.73 g/h/d; digestibility of PK P0 67.28%, P1 71.83%, P2 69.31%, P3 65.61%; SK consumption P0 112.90 g/h/d, P1 118.47 g/h/d, P2 101.30 g/h/d, P3 94.97 g/h/d and SK digestibility P0 54 .60 %, P1 58.40 %; P2 52.96 %, P3 48.20 %. The analysis of variance showed that the treatment had no significant effect (P>0.05) on the consumption and digestibility of PK and SK female local goats. This study concluded that the provision of complete feed based on silage mixed with sorghum and Gamal leaves at different levels added had the same effect on the consumption and digestibility of PK and SK of female local goats.